Improving the Methodology of Teaching the Science of Vertebrate Zoology in Higher Education Institutions as A Pedagogical Problem - Norquziyeva Madinaxon Sharof qizi (Zien Journals, 2023)
The article presents opinions and comments on the goals and tasks of vertebrate zoology. In addition, the opinions of scientists on the methodology of teaching vertebrate zoology were expressed
Keywords: methodology; working with information; skills